"Am I entitled to take a break in caregiving?": Perceptions of leisure activities of family caregivers of loved ones with dementia in China. (July 2022) - Xu, Xin Yi; Leung, Doris; Leung, Angela Yee Man; Kwan, Rick Yiu Cho; Liang, Ting Na; Chai, Ai Jun
Leisure activities are essential for family caregivers of loved ones with dementia living in the community, yet these caregivers tend not to engage in them, especially in China, wherein it may have a negative impact on their physical and psychological health. To date, limited knowledge exists regarding underlying reasons that deter these family caregivers from doing leisure activities. This study aims to explore perceptions of family caregivers of people living with dementia and their engagement in leisure activities. A qualitative descriptive research design was used with semi-structured, face-to-face, individual in-depth interviews. The data were collected in Shijiazhuang, China between October and November 2019. Content analysis was used to develop categories. Results of 20 family caregivers (5 men and 15 women, mean age = 55.6±12.7) reported their perceptions under four main categories: (i) "the condition of leisure life, " (ii) "needs for leisure activities, " (iii) "reasons for the reluctance to do leisure activities, " and (iv) "motivations supporting the implementation of leisure activities." In addition to the heavy caregiving workload and lack of support, traditional Chinese beliefs including filial commitment and "fatalistic voluntarism" were the reasons that prevented Chinese family caregivers of people living with dementia from doing leisure activities. However, engaging their loved ones in leisure activities, like doing exercise together, could motivate family caregivers themselves to participate in leisure activities. These findings encourage healthcare professionals to consider the influence of culture on family caregivers' engagement in leisure activities which is one of the ways to reduce stress. Family caregivers may benefit from the leisure activities by learning how to better cope with and balance caregiving tasks with their leisure pursuits in the community.